Synthetic Routes to, Transformations of, and Rather Surprising Stabilities of (N-Methyl-N-phenylcarbamoyl)sulfenyl Chloride, ((N-Methyl-N-phenylcarbamoyl)dithio)carbonyl Chloride, and Related Compounds - Schrader, Alex M; Schroll, Alayne L; Barany, George (Journal of organic chemistry, 2011)
The title compound classes, (carbamoyl)sulfenyl chlorides and ((carbamoyl)dithio)carbonyl chlorides, have been implicated previously as unstable, albeit trappable, intermediates in organosulfur chemistry. The present work reports for each of these functional groups: (i) several routes to prepare it in the N-methylaniline family; (ii) its direct structural characterization by several spectroscopic techniques; (iii) its rather unexpected stability and its ultimate fate when it decomposes; (iv) a series of further chemical transformations that give highly stable derivatives, each in turn subject to thorough characterization. Relevant kinetic and mechanistic experiments were carried out, including some with p-methyl- and 2,6-dimethyl-substituted N-methylanilines. Given that the title compounds can be isolated and are relatively stable, they may find applications in the preparation of thiolyzable and/or photolabile protecting groups for the sulfhydryl function of cysteine and for the development of new protein synthesis and modification reagents.